2021
DOI: 10.1002/chem.202102032
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Water Oxidation in Chitosan Nanostructures Containing Covalently Linked RuII Chromophores and Encapsulated Iridium Oxide Nanoparticles

Abstract: The luminophore Ru(bpy)2(dcbpy)2+ (bpy=2,2’‐bipyridine; dcbpy=4,4’‐dicarboxy‐2,2’‐bipyridine) is covalently linked to a chitosan polymer; crosslinking by tripolyphosphate produced Ru‐decorated chitosan fibers (NS‐RuCh), with a 20 : 1 ratio between chitosan repeating units and RuII chromophores. The properties of the RuII compound are unperturbed by the chitosan structure, with NS‐RuCh exhibiting the typical metal‐to‐ligand charge‐transfer (MLCT) absorption and emission bands of RuII complexes. When crosslinks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Indeed, flash photolysis experiments showed that such a hole-scavenging process is faster in IrO 2 ⊂NP-RuCh . For this latter species, the rate constant of the hole scavenging process is 7.4 × 10 4 s −1 , 25 a remarkable value when compared to the rate constant for the hole scavenging process in the [Ru(bpy) 3 ] 2+ /IrO 2 /Na 2 S 2 O 8 separated system, which is reported to be 8 × 10 2 s −1 , 26 that is two orders of magnitude slower. The relevant acceleration of the hole scavenging in IrO 2 ⊂NP-RuCh is attributed to the increase in the proximity of both photosensitizer and catalyst subunits, thanks to the restricted environment promoted by the chitosan nanofibers, which play the role of concentrators.…”
Section: Forced Co-localization Of Photosensitizers and Catalystsmentioning
confidence: 89%
See 4 more Smart Citations
“…Indeed, flash photolysis experiments showed that such a hole-scavenging process is faster in IrO 2 ⊂NP-RuCh . For this latter species, the rate constant of the hole scavenging process is 7.4 × 10 4 s −1 , 25 a remarkable value when compared to the rate constant for the hole scavenging process in the [Ru(bpy) 3 ] 2+ /IrO 2 /Na 2 S 2 O 8 separated system, which is reported to be 8 × 10 2 s −1 , 26 that is two orders of magnitude slower. The relevant acceleration of the hole scavenging in IrO 2 ⊂NP-RuCh is attributed to the increase in the proximity of both photosensitizer and catalyst subunits, thanks to the restricted environment promoted by the chitosan nanofibers, which play the role of concentrators.…”
Section: Forced Co-localization Of Photosensitizers and Catalystsmentioning
confidence: 89%
“…In particular, a hydrogel formed by polymerized chitosan, functionalized with bpy moieties serving to anchor Ru(bpy) 3 2+ -type chromophores on the chitosan structure, has been prepared in the presence of iridium oxide nanoparticles, the water oxidation catalysts. 25 In these conditions, iridium oxide nanoparticles are incorporated within the hydrogel, forming a nanofiber-like structure, IrO 2 NP-RuCh. 25 Figure 11 shows the structural formula of the chitosan polymer containing the Ru(II) chromophore.…”
Section: Forced Co-localization Of Photosensitizers and Catalystsmentioning
confidence: 99%
See 3 more Smart Citations